Pengembangan Paket Tes Berbasis Hihgher Order Thinking Skills (HOTS) Pokok Bahasan Theorema Phytagoras - kusuma, rhema nadya (Kadikma, 2021)
Lack of students' skills in answering questions that require analysis, evaluation, and creativity so that in learning they cannot answer questions that require higher-order thinking skills. This results in the level of thinking of students in Indonesia is still low, as seen from Indonesia's ranking in the TIMSS in 2015. One of the efforts made to improve these higher thinking skills is by using the HOTS test package. This type of research is a development research with the Thiagrajan or Four D Model which aims to describe the process and results of developing HOTS-based test packages for eighth grade students on the Theorema Pythagoras material which is valid, practical, and effective in training students' higher order thinking skills. The method used in this research is the test method to determine the validity and effectiveness of the test package and the questionnaire method to determine practicality. The results of this study are in the form of students' achievements in analyzing, evaluating, and creating in accordance with higher-order thinking indicators with good interpretations. The HOTS-based test package, the subject of Pythagorean Theorema, produced in this study is valid, practical, and effective and can be used to improve students' higher order thinking skills. Keywords: Test Package, Pythagorean Theorem, Higher Order Thinking Skills (HOTS)